x-y-5=0.......(1)

2x-y+17=0......(2)

We will use the elimination method to solve:

First , subtract (1) from (2):

x + 22 =0

==> x= -22

==> y= x-5= -22-5= -27

To check answer:

x-y-5=0

-22-(-27 )-5=0

-22+27 -5=0

-27+27=0

Also check (2):

2x-y+17=0

2(-22) -(-27) +17 =0

-44 + 27 +17=0

-44 + 44=0

Then the answer is x=-22 and y= -27

The system of equations x-y-5 =0 and 2x-y + 17=0 has to be solved.

x-y-5 =0 ...(1)

2x-y + 17=0 ...(2)

Subtract (2) from (1)

x - y - 5 - 2x + y - 17 = 0

-x - 22 = 0

x = -22

Substitute in x - y - 5 = 0

-22 - y - 5 = 0

y = -27

The solution of the given set of equations is x = -22 and y = -27

To solve the system, we'll re-write the first equation as:

x = y+5

We'll substitute x by it's expression into the second equation:

2(y+5) - y + 17 = 0

We'll open the brackets:

2y + 10 - y + 17 = 0

y + 27 = 0

We'll subtract 27 both sides:

**y = -27**

We'll substitute y by it's value into the first re-written equation:

x = y+5

x = -27+5

**x = -22**

**The solution of the system is : (-22,-27)**

To solve x-y-5 =0 and 2x-y +17 =0

Solution:

x-y - 5 = 0.....(1)

2x-y +17 = 0.....(2)

(2) - (1) eleminayes y :

2x-y+17 -(x-y-5) = 0

2x-y+17-x+y+5 = 0

x+22 = 0

Substitute x= -22 in (1)

-22-y-5 = 0. Or

y = -27. Or

x=-22 and y = -27